MANAJEMEN KURIKULUM ENGLISH LOVER - M Idris Sulaiman; Ali Imron; Teguh Triwiyanto (Universitas Negeri Malang, 2018)
Abstract: The purpose of this study is: (1) knowing the planning; (2) the implementation; (3) the evaluation; (4) the obstacle and (5) solutions to obstacles in the implementation of the English Lover program curriculum in Annur Bululawang Vocational High School, Malang Regency. This research approach method is qualitative case study. Data collection techniques used were (1) interviews, (2) observations, and (3) documentation. The results of the study are English Lover curriculum planning, namely: (1) Meetings, (2) Formation of schedules, (3) Making learning models, and (4) division of teams. English Lover is implemented and adjusted as the schedule that has been made the learning process can be carried out inside and outside the classroom in accordance with instructions from the English Lover tutor. English Lover learning evaluation is conducted every month, barriers to English Lover learning itself are in the internal factors of the school, in planning and implementation, and the solution is in the form of improvements in the planning system and in the implementation of the English Lover curriculum.Key Words: Curriculum Management English LoverAbstrak: Tujuan penelitian ini yaitu: (1) mengetahui perencanaan; (2) pelaksanaan; (3) evaluasi; (4) hambatan dan (5) pemecahan terhadap hambatan dalam pelaksanaan kurikulum program English Lover di SMK Annur Bululawang Kabupaten Malang. Metode pendekatan penelitian ini yaitu kualitatif studi kasus. Teknik pengumpulan data yang digunakan adalah (1) wawancara, (2) observasi, dan (3) dokumentasi. Hasil penelitian yaitu Perencanaan kurikulum English Lover yaitu: (1) Rapat, (2) Pembentukan jadwal, (3) Membuat model pembelajaran, dan (4) pembagian tim. English Lover dilaksanakan dan disesuaikan seperti jadwal yang telah dibuat proses pembelajarannya pun bisa dilaksanakan didalam maupun diluar kelas sesuai dengan intruksi dari tutor English Lover. Evaluasi pembelajaran English Lover dilakukan pada tiap bulannya, Hambatan dalam pembelajaran English Lover sendiri berada dalam faktor internal sekolah, dalam perencanaan serta pelaksanaannya, dan pemecahannya berupa perbaikan dalam sistem perencanaan maupun dalam pelaksanaan kurikulum English Lover.Kata kunci: Manajemen Kurikulum English Lover